2019
DOI: 10.3389/fphar.2019.00638
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Exerts Neuroprotective Effects in FeCl3-Induced Posttraumatic Epileptic Seizures via Suppressing Ferroptosis

Abstract: Posttraumatic epilepsy (PTE) is a prevalent type of acquired epilepsy secondary to traumatic brain injury, and is characterized by repeated seizures. Traditional antiepileptic drugs have minimal response in preventing posttraumatic epileptic seizures. It is essential for the development of new therapeutic strategy. Our previous work disclosed a potent neuroprotective role of baicalein, a flavonoid extracted from Scutellaria baicalensis Georgi, against inherited epilepsy in rats. Whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 84 publications
(102 reference statements)
4
89
0
Order By: Relevance
“…Ferroptosis is activated in KA-induced seizure mice and human epileptic patients. Our prior work showed the presence of ferroptosis in various epileptic seizure models induced by chemical reagents including pentylenetetrazol, pilocarpine and FeCl 3 (22,23). To determine whether ferroptosis process was activated in KA-induced seizures, a common model resembling human intractable epilepsy, we detected a set of ferroptotic indices in the hippocampus of this model including morphological characteristics of mitochondrion, lipid peroxidation by-products including 4-HNE and MDA levels and Ptgs2 mRNA.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Ferroptosis is activated in KA-induced seizure mice and human epileptic patients. Our prior work showed the presence of ferroptosis in various epileptic seizure models induced by chemical reagents including pentylenetetrazol, pilocarpine and FeCl 3 (22,23). To determine whether ferroptosis process was activated in KA-induced seizures, a common model resembling human intractable epilepsy, we detected a set of ferroptotic indices in the hippocampus of this model including morphological characteristics of mitochondrion, lipid peroxidation by-products including 4-HNE and MDA levels and Ptgs2 mRNA.…”
Section: Resultsmentioning
confidence: 95%
“…It is likely that seizure can initiate non-apoptotic forms of regulated cell death. Our recent work has delineated that ferroptosis, a novel cell death mode, is induced in FeCl 3 -, PTZ-and pilocarpine-induced seizure models (22,23). Similarly, in our current study, we also only provides a previously unknown cell death mechanism suggesting that ferroptosis is activated in epileptic seizures, but also strongly implicates that reducing ferroptosis is a valid therapeutic target for seizure-related disorders such as epilepsy, ischemic stroke, traumatic brain injury and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence shows that ferrostatin-1 (Fer-1), a specific inhibitor of ferroptosis, alleviates cognitive impairment caused by kainic acid (KA)-induced seizures in rats (Ye et al, 2019) and attenuates seizures in pentylenetetrazole and pilocarpine-treated epileptic mice (Mao, Zhou, & Jin, 2019a). Additionally, baicalein can ameliorate posttraumatic epileptic seizure behavior by inhibiting the ferroptosis process (Li et al, 2019). Whereas the former studies have demonstrated that regulation of oxidative stress contributes to the therapeutic effect of lapatinib (Aird et al, 2012;Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%